Html, Xhtml, And Css Bible, 3rd Edition - Pfaffenberger, Brian (Wiley Publishing, 2011)
An expanded, updated, and retitled edition of HTML Bible, examining HTML, XHTML-a set of extensions to HTML to make it more like XML-and cascading style sheets (CSS), which provide a simple way to add consistent formatting to HTML Web documents Focusing on reader feedback and changing industry trends, this new edition is a major overhaul that addresses the extensive changes in Web development Shows readers the best, most efficient way to use HTML and examines which peripheral technologies are worth learning for the long run Features "before and after" pictures that show the results of improved Web page coding Offers continued coverage of key topics, including site administration, dynamic data-driven pages, and many others, in addition to new sections on hot new topics such as blogs and content management